PENGARUH EKSPOR KELAPA INDONESIA KE NEGARA – NEGARA EROPA TERHADAP PENDAPATAN NEGARA INDONESIA TAHUN 2013 - 2017 - Suhendra "; Faisal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Coconut commodity is one of the leading commodities from the plantation sector which is the subsector of the agricultural sector. This commodity contributes tremendously to Gross Domestic Product (GDP) through foreign exchange earnings from export side and through tax from domestic consumption side by coconut industry and other derivative products. The purpose of this study is to find out about Indonesian coconut, the effect of Indonesian coconut exports on State revenues. This research uses descriptive qualitative research methodology with this research technique is library research. It can be concluded that the area of coconut plantation in Indonesia from year to year has increased expansion, so that this has a direct impact on Indonesia coconut production which from year to year also increased, this can be seen from the production trend that has increased per year, and the value of the production ajuga continues to increase every year. As coconut production increases in people's consumption power, Indonesia increases coconut export volume. From the analysis results can be seen that the export of coconut Indonesia also increased from year to year, then the value of exports also increased every year. The import behavior of the PRC, India and the European Union shows that the variables of gross domestic product have a strong and dominant influence in the demand for coconut imports of each country. Therefore, it is suggested that the Indonesian government can make a policy to further encourage export increase especially in the coconut industry which is the largest industry in Indonesia so it is expected that the government can finance the development intensification and extensification in the coconut industry. Keywords: Coconut and export